PERSONAL HYGIENE, SANITATION AND FOOD SAFETY KNOWLEDGE OF FOOD WORKERS AT THE UNIVERSITY CANTEEN IN INDONESIA - Abdul Rahman; Ramadhan Tosepu; Siti Rabbani Karimuna; Sartiah Yusran; Asnia Zainuddin; Junaid Junaid (Public Health of Indonesia)
Background: Food and beverage sanitation hygiene is a prevention effort that focuses on activities or actions that are necessary to free food and drinks from hazards that can interfere with or damage health.